Employment protection and transition towards corporate goodwill in the gig economy - Ab Rahman, Rozanah; Che Aziz, Danial Ariff; Wong, Foong Yee (Penerbit UPM, 2024)
This case on employees’ social protection and human resource management issues discusses the challenges of a delivery service company, FoodieFleet, which is part of the gig economy. The case was about the application of the SelfEmployment Social Security Act 2017 and the Employment Act 1955 to full-time employees versus temporary employees. The case also looked at the advantages and disadvantages of hiring full-time and temporary employees. This case has a moderate level of difficulty and may be used for teaching employment law, industrial relations law, business law and human resource management.